Barriers and facilitators for parents in end-of-life decision-making for neonates at the Neonatal Intensive Care Unit: A qualitative study. (April 2022) - Piette, Veerle; Dombrecht, Laure; Deliens, Luc; Cools, Filip; Chambaere, Kenneth; Goossens, Linde; Naulaers, Gunnar; Laroche, Sabine; Cornette, Luc; Bekaert, Eline; Decoster, Pauline; Beernaert, Kim; et al.
Background: Mortality and end-of-life decision-making can occur in newborns, especially within the Neonatal Intensive Care Unit. For parents, participating in end-of-life decision-making is taxing. Knowledge is lacking on what support is helpful to parents during decision-making. Aim: To identify barriers and facilitators experienced by parents in making an end-of-life decision for their infant. Design: Qualitative study using face-to-face semi-structured interviews. Setting/participants: We interviewed 23 parents with a child that died after an end-of-life decision at a Neonatal Intensive Care Unit between April and September 2018. Results: Parents stated barriers and facilitators within 4 themes: 1. Clinical knowledge and prognosis; 2. Quality of information provision; 3. Emotion regulation; and 4. Psychosocial environment. Facilitators include knowing whether the prognosis includes long-term negative quality of life, knowing all treatment options, receiving information according to health literacy level, being able to process intense emotions, having experienced counseling and practical help. Barriers include a lack of general medical knowledge, being unprepared for a poor prognosis, having an uninformed psychologist. Conclusions: We found that clinical information and psychosocial support aid parents in decision-making. Information is best tailored to health literacy. Psychosocial support can be provided by experienced, informed counselors, social services and sibling support, distinguishing between verbal and non-verbal coping preferences, and calm, familiar architecture. Intense emotions may hinder absorption of clinical information, therefore interventions to aid emotion regulation and reduce cognitive load may be looked at in further research. Adjustment of the Situations, Opinions and Options, Parents, Information, Emotions framework based on our results can be evaluated.